Differential expression of miR-1297, miR-3191-5p, miR-4435, and miR-4465 in malignant and benign breast tumors - Mosapour, Abbas (Iran J Basic Med Sci, 2020)
OBJECTIVE(S): MicroRNAs (miRs) are a class of small non-coding RNAs which are associated with tumor growth and progression. In the present study, we assessed the expression of selected miRs in malignant, benign, and adjacent normal breast tissues. MATERIALS AND METHODS: The expression of miR-1297, miR-3191-5P, miR-4435, and miR-4465 were evaluated in malignant (n=50), benign (n=35), and adjacent normal breast tissues (n=20) using qRT-PCR. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were generated for evaluating the diagnostic values of miRs. To evaluate diagnostic efficacy, miRs-based score was obtained using the logistic regression model. RESULTS: Among malignant tumors, the expression of miR-1297, miR-3191-5p, and miR-4435 was significantly lower (P=0.024, P<0.001 and P=0.031), respectively. The expression of miR-4465 was higher (P=0.023) than that of normal tissue. The expression of these miRs was lower than those of benign tumors (P<0.01, P<0.001, P<0.0001, and P<0.01, respectively). We observed a positive correlation between miR-4465 expression levels and tumor stage (P=0.042) and a negative correlation with grade and Ki-67 score (P<0.05). The AUCs for miR-1297, miR-3191-5p, miR-4435, and miR-4465 in malignant tumors versus normal tissues were 0.784, 0.700, 0.976, and 0.865 and versus benign tumors they were 0.938, 0.857, 0.981, and 0.785, respectively. The optimal logit(P) value of 0.262 distinguished malignant from normal subjects with a sensitivity of 0.91, specificity of 0.85, and an overall accuracy of 0.89. CONCLUSION: The panel of these miRs are suggested as possible onco-miRs(miR-4465) or tumor suppressor-miRs (miR-3191-5P, miR-1297, miR-4435). Overall, our results indicated that these miRs could be introduced as diagnostic biomarkers in breast cancer patients.